First sighting records of the nationally Endangered Ibisbill (Ibidorhyncha struthersii) in Chameliya River, Darchula, Nepal. - Adhikari, Bhabishya; Bhattarai, Charan; Shrestha, Mohan Bikram (Nepal Journal of Environmental Science, 2026)
The Ibisbill (Ibidorhyncha struthersii) is a habitat-specialist wader, usually associated with high-altitude shingle-bed rivers in the Himalayas and Central Asia. Despite being widely distributed, a sighting from the Chameliya River in far-western Nepal has unreported until now. Ibisbill at the Chameliya River in Darchula District were photographed on 5 November 2025 during bird watching along the river. A single adult Ibisbill was photographed at Bangabagar (29.660056°N, 80.532167°E) as the first confirmed record of the species at the extreme west of Nepal. The individual was observed at the riparian belt of the Chameliya River with cobble and boulder substrates with tranquil flow of the river, a habitat preferred by this species. Photographs and GPS coordinates are the supporting evidences to validate the sighting. Anthropogenic pressures such as the extraction of riverbed materials, trashes including plastics and shattered glass pieces, fishing activities were noted that are considered to be threats to Ibisbill in the site. This record highlights the Chameliya River as a previously unrecognized wintering site for Ibisbill.